Trends in global clinical trial registration: an analysis of numbers of registered clinical trials in different parts of the world from 2004 to 2013. Issue 9 (25th September 2015) - Viergever, Roderik F; Li, Keyang
Abstract : Objectives: To analyse developments (and their causes) in the number and proportion of clinical trials that were registered in different parts of the world after the International Committee of Medical Journal Editors (ICMJE) announced in 2004 that it would require registration of clinical trials as a condition for publication. Setting: The International Clinical Trials Registry Platform (ICTRP). Design: The ICTRP database was searched for all clinical trials that were registered up to 31 December 2013. Results: The ICTRP database contained data on 186 523 interventional clinical trials. The annual number of registered clinical trials increased from 3294 in 2004 to 23 384 in 2013. Relative to the number of clinical trial research publications, the global number of registered clinical trials increased fivefold between 2004 and 2013, rising particularly strongly between 2004 and 2005. In certain regions, especially Asia, the annual number of registered trials increased more gradually and continued to increase up to 2013. In India and Japan, two countries with marked but more gradual increases, these increases only happened after several local measures were implemented that encouraged and enforced registration. In most regions, there was a trend toward trials being registered at local registries. Conclusions: Clinical trial registration has greatly improved transparency in clinical trial research. However, these improvements have not taken place equally in all parts of the world. Achieving compliance with registration requires a coalescence of global and local measures, and remains a key challenge in many countries. Poor quality of registered trial data and the inaccessibility of trial protocols, results and participant-level data further undermine the potential benefits of clinical trial registration. National and regional registries and the ICTRP have played a leading role in achieving the successes of trial registration to date and should be supported in addressing these challenges in the future.